Biological and molecular interplay between two viruses and powdery and downy mildews in two grapevine cultivars. (1st November 2020) - Gilardi, Giovanna; Chitarra, Walter; Moine, Amedeo; Mezzalama, Monica; Boccacci, Paolo; Pugliese, Massimo; Gullino, Maria Lodovica; Gambino, Giorgio
Abstract: Grapevine may be affected simultaneously by several pathogens whose complex interplay is largely unknown. We studied the effects of infection by two grapevine viruses on powdery mildew and downy mildew development and the molecular modifications induced in grapevines by their multiple interactions. Grapevine fanleaf virus (GFLV) and grapevine rupestris stem pitting-associated virus (GRSPaV) were transmitted by in vitro-grafting to Vitis vinifera cv Nebbiolo and Chardonnay virus-free plantlets regenerated by somatic embryogenesis. Grapevines were then artificially inoculated in the greenhouse with either Plasmopara viticola or Erysiphe necator spores. GFLV-infected plants showed a reduction in severity of the diseases caused by powdery and downy mildews in comparison to virus-free plants. GFLV induced the overexpression of stilbene synthase genes, pathogenesis-related proteins, and influenced the genes involved in carbohydrate metabolism in grapevine. These transcriptional changes suggest improved innate plant immunity, which makes the GFLV-infected grapevines less susceptible to other biotic attacks. This, however, cannot be extrapolated to GRSPaV as it was unable to promote protection against the fungal/oomycete pathogens. In these multiple interactions, the grapevine genotype seemed to have a crucial role: in 'Nebbiolo', the virus-induced molecular changes were different from those observed in 'Chardonnay', suggesting that different metabolic pathways may be involved in protection against fungal/oomycete pathogens. These results indicate that complex interactions do exist between grapevine and its different pathogens and represent the first study on a topic that still is largely unexplored.